Effects of supplement type during the pre-finishing growth phase on subsequent performance of Nellore bulls finished in confinement or on tropical pasture - Ferrari, Adriana Cristina [UNESP]; Berça, Andressa Scholz [UNESP]; Silva, Maria Luisa Curvêlo [UNESP]; Leite, Rhaony Gonçalves [UNESP]; Dallantonia, Erick Escobar [UNESP]; Romanzini, Eliéder Prates [UNESP]; Barbero, Rondineli Pavezzi; da Silva Cardoso, Abmael; Lage, Josiane Fonseca; Tedeschi, Luís Orlindo; Reis, Ricardo Andrade [UNESP] (American Registry of Professional Animal Scientists, 2022)
Objective: Our objective was to evaluate the effect of supplement type fed during the pre-finishing growth phase of grazing Nellore bulls on gain performance during the subsequent finishing phase, either in confinement or on pasture. During the pre-finishing growth phase, bulls were grazed on pastures of Urochloa brizantha cv. Marandu. Bulls were supplemented with 1 of 4 supplements: (1) ad libitum mineral mixture (MM), (2) ground corn (GC), (3) GC with soybean meal (SBM), or (4) GC with dried distillers grain (DDGM). All supplements were administered at 3 g/kg of body weight (BW) on a dry matter (DM) basis. Materials and Methods: Eighty bulls were distributed in a completely randomized, 4 × 2 factorial arrangement, with 4 pre-finishing supplementation treatments (MM, GC, SBM, or DDGM) and 2 finishing systems (pasture or confinement). Ten cattle from each postweaning treatment were kept on pasture (n = 3 paddocks/treatment), and 10 bulls were housed in confinement pens (n = 3 pens/treatment). Bulls finished on pasture were offered a concentrate supplement consisting of 337.6 g/kg dried distillers grain (DDG), 611.2 g/kg GC, and 56.1 g/kg MM. The final diets offered in the confinement system consisted of 300 g/kg corn silage, 427.8 g/kg GC, 263.3 g/kg DDG, and 35.8 g/kg MM (DM basis). Results and Discussion: During the finishing phase, bulls that received GC and DDGM in pasture consumed more CP than bulls in the confinement system (P = 0.001). Nutrient digestibility was greater among the bulls in pasture than those in confinement (P ≤ 0.001), likely because of the lower proportion of NDF consumed by bulls that expressed selective grazing behavior (P = 0.001). Daily weight gain was affected by pre-finishing history (P = 0.03) and finishing system (P ≤ 0.001) and was lower after SBM supplementation for bulls on pasture (P = 0.009). The final BW (P ≤ 0.001), hot carcass weight (P = 0.005), and fat thickness (P ≤ 0.001) were greater in bulls finished in confinement, but carcass yield was greater in bulls from pasture (P ≤ 0.001). Implications and Applications: Preweaning supplementation affected the intake of nutrients in Nellore bulls finished on pasture postweaning but did not affect the intake of bulls finished in a confinement feedlot. Supplementation with DDGM in the preweaning phase (3 g/kg of BW) did not affect animal performance or carcass traits in either finishing system. Therefore, it is an option for replacing conventional supplements.
Keywords: dried distillers grains; feedlot; Nellore breed; tropical pasture; zebu cattle